BL_GERICHTE 720 2014 232 vom 26. März 2015 , Entscheid des Kantonsgerichts Basel-Landschaft, Abteilung Sozialversicherungsrecht vom 26. März 2015 (720 14 232) - BL Gerichte (2015)
Hilflosenentschädigung